Methanothermobacter thermautotrophicus modulates its membrane lipids in response to hydrogen and nutrient availability - Yoshinaga, Marcos Y.; Gagen, Emma J.; Wörmer, Lars; Broda, Nadine K.; Meador, Travis B.; Wendt, Jenny; Thomm, Michael; Hinrichs, Kai-Uwe (Frontiers in Microbiology, 2015)
Methanothermobacter thermautotrophicus strain ∆H is a model hydrogenotrophic methanogen, for which extensive biochemical information, including the complete genome sequence, is available. Nevertheless, at the cell membrane lipid level, little is known about the responses of this archaeon to environmental stimuli. In this study, the lipid composition of M. thermautotrophicus was characterized to verify how this archaeon modulates its cell membrane components during growth phases and in response to hydrogen depletion and nutrient limitation (potassium and phosphate). As opposed to the higher abundance of phospholipids in the stationary phase of control experiments, cell membranes under nutrient and energy stress were dominated by glycolipids that likely provided a more effective barrier against ion leakage. We also identified particular lipid regulatory mechanisms in M. thermautotrophicus, which included the accumulation of polyprenols under hydrogen-limited conditions and an increased content of sodiated adducts of lipids in nutrient-limited cells. These findings suggest that M. thermautotrophicus intensely modulates its cell membrane lipid composition to cope with energy and nutrient availability in dynamic environments.